2021
DOI: 10.1002/nur.22120
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ferrans et al.'s conceptual model of health‐related quality of life: A systematic review

Abstract: Ferrans, Zerwic, Wilbur, and Larson proposed the conceptual model of healthrelated quality of life (HRQOL) in 2005 to explicate the constructs associated with HRQOL and to describe the associations among those constructs. In this systematic review, the authors aimed to describe empirical studies that used Ferrans et al.'s model and to examine the evidence related to the hypothesized model concepts. This review followed Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Relevant arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This framework continues to evolve with adaptations such as the 2005 model by Ferrans et al [ 24 ], that expanded the hypothesized life domains that account for HRQL. A recent systematic review of this version of the taxonomy reported that among 31 studies (pooled n = 62,281), 19 of 20 hypothesized associations between life domains and HRQL were supported [ 25 ]. Interestingly, this evidence was obtained from studies where a clinically applied theory or framework for health behavior or HRQL was referenced in only 16.5% of papers, while only 6% applied a theory to account for the constructs used in assessing HRQL.…”
Section: Hrql In Clinical Settings and The Encounter With Construct P...mentioning
confidence: 99%
“…This framework continues to evolve with adaptations such as the 2005 model by Ferrans et al [ 24 ], that expanded the hypothesized life domains that account for HRQL. A recent systematic review of this version of the taxonomy reported that among 31 studies (pooled n = 62,281), 19 of 20 hypothesized associations between life domains and HRQL were supported [ 25 ]. Interestingly, this evidence was obtained from studies where a clinically applied theory or framework for health behavior or HRQL was referenced in only 16.5% of papers, while only 6% applied a theory to account for the constructs used in assessing HRQL.…”
Section: Hrql In Clinical Settings and The Encounter With Construct P...mentioning
confidence: 99%
“…Future studies are recommended to recruit adolescents from a wider range of socio-demographic backgrounds. Third, this study did not consider students' disease characteristics, function status and global health perceptions, which are essential pathway factors of HRQoL ( Duangchan & Matthews, 2021 ). Fourth, the standardized correlation coefficients in the final trimmed path model were small (ranging from 0.03 to 0.45), suggesting weak to moderate relationships between variables.…”
Section: Discussionmentioning
confidence: 99%